Experimental study on variable-mass seepage model of water-rich altered granite - Xu, Hanhua; Zeng, Yunchuan; Shen, Wei; Tang, Haojun; Bao, Xun; Zhang, Quan; Yan, He (Frontiers in Earth Science, 2026)
To deeply investigate the catastrophe mechanism of water inrush and mud outburst when tunnels traverse water-rich altered granite strata, this paper utilizes a self-developed visualized variable mass seepage test system to conduct physical model tests under varying conditions of water pressure and initial porosity. Unlike conventional geotechnical media, the study finds that the seepage failure of altered granite exhibits significant “variable mass” characteristics. Its catastrophic evolution follows a three-stage cyclic mechanism: “seepage channel connection - rock particle migration - local skeleton collapse.” The experimental results indicate that: (1) Water pressure is the dominant factor driving particle migration and mass loss; high water pressure significantly accelerates the transition from porous media seepage to pipe (conduit) flow. (2) Initial porosity has a complex non-linear impact on the catastrophic consequences. While higher initial porosity increases the volume of water inrush and the final stable porosity, it paradoxically leads to a relative decrease in the total volume of discharged mud. This is because it induces more frequent internal skeletal collapse and clogging effects. The variable mass seepage evolution model established in this study identifies particle loss as the fundamental cause of sudden surges in permeability, providing a theoretical basis for disaster prevention and control in this type of strata.